DIRECTIVE SPEECH ACTS ON WARNING BOARDS OF MODERN RAILWAYS - Yuki Priliani Putri; I Dewa Putu Wijana (PROJECT (Professional Journal of English Education), 2024)
A speech act embodies many functions such as requesting, stating, inquiring, suggesting, reminding, and so on, that can be conveyed in various forms and through different objects. This study aimed to analyze the use of directive speech acts written on warning boards on modern rail transportation. The data of this study were in sentences on warning boards that contain directive speech acts, and obtained from February 20th – March 10th, 2023 on three selected modern railways in Yogyakarta; 1) Commuter Line (KRL), 2) Railink airport train, and 3) Prambanan Express (Prameks) train. This study applied the qualitative method to describe the explanations and the quantitative method to calculate the data found. The findings of this study revealed the use of directive speech acts on warning boards on modern railways functions to forbid (37.5%), order (18.8%), request (28.1%), suggest (3.1%), and warn (12.5%). The function of forbid is the most frequently used on the warning board with 12 data.  The sentences were conveyed through direct, indirect, implicit, and explicit strategies. Several factors influenced how the speech acts uttered considering the speaking components.